Study of prescribing patterns of antimicrobial agents in the Paediatric wards at a tertiary care hospital, Dhaka - T, Afrin; I, Jahan; SA, Khatun; RA, Begum (Journal of Dhaka National Medical College & Hospital, 2018)
Background: Antibiotics are generally used in pediatric illness and unreasonable use of antibiotics can lead to bacterial resistance. Rational prescribing practices provide to contest this global public health challenge by preventing antibiotic overuse and misuse. Objective: Aim of the study to find out the prescribing patterns of antimicrobial agents in the Paediatric wards at a tertiary care hospital. Methodology: This retrospective study was carried out by collecting prescriptions of the indoor patients admitted in the wards paediatric department at Sir Salimullah Medical College & Hospital, Dhaka to assess the prescribing patterns of antimicrobial agents. Total 110 prescriptions containing antimicrobial agents were collected from the hospital record section for the study during January 2014 to March 2014. Prescriptions were collected irrespective of the indications. The data were collected in predesigned questionnaires, containing information regarding age and sex of the patients as well as trade/generic name of antimicrobial drugs, numbers of drugs prescribed, their dosage, frequency, route of administration, duration of therapy along with the clinical diagnosis. Results: Majority 74(67.3%) patients had respiratory infection, 15 (13.6%) had GIT infection, 11(10.0%) had fever, 4(3.6%) had urinary tract infection and 6(5.5%) others disease. Most 24(17.8%) of the patients prescribed ceftriaxone, 15(11.1%) cefuroxime, 9(6.9%) amoxicillin, 12(9.2%) ampicillin, 11(8.35%) ciprofloxacin, 8(6.2%) metronidazole, 7(5.4%) azithromycin and 7(5.4%) amikacin, 37.7% patients prescribed cephalosporins, 26.9%) beta-lactams (except CP)+ vancomycin, 14.6% metronidazole, 5.4% macrolides and 9.2% amnioglycosides. Conclusion: Respiratory infections were the most common disease seen followed by GIT infection, fever, urinary tract infection. Injectable cephalosporins and beta-lactams are more common prescribing antibiotics. Addressed properly to prevent bacterial resistance and guidelines for the treatment of pediatric patients should be updated. J. Dhaka National Med. Coll. Hos. 2018; 24 (02): 19-22